USING CORRECTIVE FEEDBACK TOWARDS STUDENTS’ WRITINGS ON JOURNAL BOOKS - Sintawati, Fairus; Wulandari, Ratih Ayu (Journal of Industrial Engineering & Management Research, 2020)
Writing skill is considered as a difficult area of English learning, including for college students. Regardless of their proficiency levels, college students make errors in their writings. Thus, English lecturers need to apply appropriate strategies in order to minimize the errors so as to improve students’ performance in writing. This study was aimed to discover one of the appropriate tools in English teaching to improve the writing skills of nursing department students of Faletehan University Serang. This is a qualitative descriptive case study. There were three instruments employed in this study, namely writing documentations, questionnaire, and interview. The results showed that students experienced different difficulties in composing their writings, especially writings with health or nursing themes. However, those difficulties didn’t hinder them to keep on writing. They made different errors in their writings, including writing aspects and grammatical features. Then, by applying the direct corrective feedbacks to the students’ writings, the lecturer had helped them in recognizing the errors they made, so that they were willing to get more feedbacks in the future. Hence, it would be helpful to improve their writing skills later.